A probe-free electrochemical immunosensor for methyl jasmonate based on a Cu-MOF–carboxylated graphene oxide platform. Issue 26 (6th June 2022) - Xing, Gengqi; Wang, Cheng; Liu, Ke; Luo, Bin; Hou, Peichen; Wang, Xiaodong; Dong, Hongtu; Wang, Jianshu; Li, Aixue
Abstract : A probe-free electrochemical immunosensor for methyl jasmonate has been developed based on a Cu-MOF-carboxylated graphene oxide platform. Abstract : Methyl jasmonate (MeJA) is an important phytohormone which can regulate plant growth and stress tolerance. It is very necessary to develop sensitive and accurate detection methods for MeJA. In this work, a probe-free electrochemical immunosensor for MeJA detection was developed based on a Cu-MOF–carboxylated graphene oxide (COOH-GO) platform. The Cu 2+ in the Cu-MOFs was used to provide redox signals, which avoids the application of an external redox probe in the electrolyte solutions as conventional immunosensors. COOH-GO was used to improve the structural stability and provide more sites for binding MeJA antibodies. The linear range of the MeJA immunosensor is from 10 pM to 100 μM, which can cover the whole concentration range of MeJA in most plants. And its detection limit is very low (0.35 pM), and it can detect very low concentrations of MeJA. This immunosensor is simple, low cost, and does not need redox probe solutions for measurements. It shows remarkable potential for on-site application in precision agriculture.